High-frequency power within the QRS complex in ischemic cardiomyopathy patients with ventricular arrhythmias: Insights from a clinical study and computer simulation of cardiac fibrous tissue. (1st August 2017) - Tsutsumi, Takeshi; Okamoto, Yoshiwo; Takano, Nami; Wakatsuki, Daisuke; Tomaru, Takanobu; Nakajima, Toshiaki
Abstract: Background: The distribution of frequency power (DFP) within the QRS complex (QRS) is unclear. This study aimed to investigate the DFP within the QRS in ischemic cardiomyopathy (ICM) with lethal ventricular arrhythmias (L-VA). A computer simulation was performed to explore the mechanism of abnormal frequency power. Methods: The study included 31 ICM patients with and without L-VA (n = 10 and 21, respectively). We applied the continuous wavelet transform to measure the time-frequency power within the QRS. Integrated time-frequency power (ITFP) was measured within the frequency range of 5–300 Hz. The simulation model consisted of two-dimensional myocardial tissues intermingled with fibroblasts. We examined the relation between frequency power calculated from the simulated QRS and the fibroblast-to-myocyte ratio ( r ) of the model. Results: The frequency powers significantly increased from 180 to 300 Hz and from 5 to 15 Hz, and also decreased from 45 to 80 Hz in patients with ICM and L-VA compared with the normal individuals. They increased from 110 Hz to 250 Hz in ICM alone. In the simulation, the high-frequency power increased when the ratio ( r ) were 2.0–2.5. Functional reentry was initiated if the ratio ( r ) increased to 2.0. Conclusions: Abnormal higher-frequency power (180–300 Hz) may provide arrhythmogenic signals in ICM with L-VA that may be associated with the fibrous tissue proliferation. Highlights: QRS time-frequency analysis reveals microscale information on cardiac excitation. High-frequency power in the QRS complex predicts lethal ventricular arrhythmias. Simulations show a link between generation of the HF-QRS and fibrous tissue density.